Understanding Consumer Choices for Innovative Electronics in Kathmandu (Voice of Teacher, 2025)
Innovative electronic devices from smartphones to smart watches have become a regular part of life for people in cities like Kathmandu. As technology evolves, so do consumer expectations, making it more important than ever for businesses to understand the key determinants influencing consumer purchasing decisions. This study examines the key factors that shape consumer behavior when purchasing innovative electronic devices in Kathmandu Metropolitan City. Drawing on survey data from local consumers, the research looks closely at how price, accessibility, customer experience, and product features affect their choices. The findings indicate that product and service offerings play a significant role in shaping purchase behavior, while traditional factors such as price, convenience, and customer experience do not exert a direct influence in the Kathmandu context. The study offers useful insights for marketers, retailers, and product developers who want to connect better with today’s tech savvy, value-driven consumers in urban Nepal.